Advertisement Remove all ads

The Sum of the Roots of the Equation` X^2-6x+2=0` (A) 2 (B)-2 (C)6 (D)-6 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads

The sum of the roots of the equation` x^2-6x+2=0` 

(a) 2 (b)-2  (c)6 (d)-6

Advertisement Remove all ads

Solution

(b)-2 

Sum of the roots of the equation `x^2-6x+2=0`  is  

`α+β=-b/a=-(-6)/1=6`  where α and  β are the roots of the equation. 

Concept: Application of Quadratic Equation
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RS Aggarwal Secondary School Class 10 Maths
Chapter 10 Quadratic Equations
Q 6

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×